Spatial Mapping of the Biomechanical Properties of the Pericellular Matrix of Articular Cartilage Measured In Situ via Atomic Force Microscopy - Darling, Eric M. (The Biophysical Society, 2010)
In articular cartilage, chondrocytes are surrounded by a narrow region called the pericellular matrix (PCM), which is biochemically, structurally, and mechanically distinct from the bulk extracellular matrix (ECM). Although multiple techniques have been used to measure the mechanical properties of the PCM using isolated chondrons (the PCM with enclosed cells), few studies have measured the biomechanical properties of the PCM in situ. The objective of this study was to quantify the in situ mechanical properties of the PCM and ECM of human, porcine, and murine articular cartilage using atomic force microscopy (AFM). Microscale elastic moduli were quantitatively measured for a region of interest using stiffness mapping, or force-volume mapping, via AFM. This technique was first validated by means of elastomeric models (polyacrylamide or polydimethylsiloxane) of a soft inclusion surrounded by a stiff medium. The elastic properties of the PCM were evaluated for regions surrounding cell voids in the middle/deep zone of sectioned articular cartilage samples. ECM elastic properties were evaluated in regions visually devoid of PCM. Stiffness mapping successfully depicted the spatial arrangement of moduli in both model and cartilage surfaces. The modulus of the PCM was significantly lower than that of the ECM in human, porcine, and murine articular cartilage, with a ratio of PCM to ECM properties of ∼0.35 for all species. These findings are consistent with previous studies of mechanically isolated chondrons, and suggest that stiffness mapping via AFM can provide a means of determining microscale inhomogeneities in the mechanical properties of articular cartilage in situ.